Pengaturan Perlindungan Hukum Bagi Tenaga Kerja Wanita Beserta Keluarganya Berdasarkan UU No. 6 Tahun 2012 Tentang Pengesahan Konvensi Internasional Perlindungan Buruh Migran Beserta Keluarganya - H, Ani Suryani (Jurnal Hukum & Pembangunan, 2016)
This study aims to assess and analyze the normative regulation of legal protection for women workers and their families based on Law No.6 of 2012 on the Ratification of the International Convention on the Protection of Migrant Workers and their Families. Processing dan data analisys done by the legal logical legal reasoning systematically and coherently and then analyzed by descriptive qualitative and subsequently concluded deductively. Based on the results obtained that: Convention on the Protection ofthe Rights of All Migrant Workers and Members of Their Families (International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families, ICRMW) defines the rights of migrant workers under two headlines: human rights of all migrant workers and members of their families (Part III), and other rights of migrant workers and their family members are undocumented or legal (Part IV). Human rights apply to all migrant workers and members of their families regardless of their legal status, while other rights applicable only to migrant workers and their family members are undocumented. The Convention does not include a new set of rights exclusively for migrant workers and members of their families.